Immunization of Mice with DNA-Based Pfs25 Elicits Potent Malaria Transmission-Blocking Antibodies - Lobo, Cheryl Ann (American Society for Microbiology, 1999)
Immunological intervention, in addition to vector control and malaria chemotherapy, will be needed to stop the resurgence of malaria, a disease with a devastating impact on the health of 300 to 500 million people annually. We have pursued a vaccination strategy, based on DNA immunization in mice with genes encoding two antigens present on the sexual stages of Plasmodium falciparum, Pfs25 and Pfg27, to induce biologically important antibodies that can block development of the parasite in the Anopheles mosquito and thus transmission of the disease. DNA encoding Pfs25 when administered by the intramuscular route, either alone or with DNA encoding Pfg27, had the most potent transmission-blocking effects, resulting in up to a 97% decrease in oocyst numbers in mosquito midguts and a 75% decrease in rate of infection. Immunization with DNA encoding a Pfg27-Pfs25 fusion protein was less effective and DNA encoding Pfg27 elicited antibodies in sera that had only modest effects on the infectivity of the parasite. These results show for the first time that DNA vaccination can result in potent transmission-blocking antibodies in mice and suggest that the Pfs25 gene should be included as part of a multicomponent DNA vaccine.